Interleukin-1β Modulates Synaptic Transmission and Synaptic Plasticity During the Acute Phase of Sepsis in the Senescence-Accelerated Mouse Hippocampus - Hoshino, Koji; Uchinami, Yuka; Uchida, Yosuke; Saito, Hitoshi; Morimoto, Yuji (Frontiers in Aging Neuroscience, 2021)
Background: Aging and pre-existing cognitive impairment are considered to be independent risk factors for sepsis-associated encephalopathy. This study aimed to investigate the manner in which aging and pre-existing cognitive dysfunction modified neuroinflammation, synaptic plasticity, and basal synaptic transmission during the acute phase of sepsis using Senescence-Accelerated Mice Prone 8 (SAMP8) and Senescence-Accelerated Resistant Mice 1 (SAMR1). Methods: We used six-month-old SAMP8 and SAMR1.Sepsis was induced using cecal ligation and puncture (CLP). The animal’s hippocampi and blood were collected for subsequent investigations 24 h after surgery. Results: Long-term potentiation (LTP) was impaired in the Shaffer-collateral (SC)-CA1 pathway of the hippocampus in SAMP8 without surgery compared to the age-matched SAMR1, which was reflective of cognitive dysfunction in SAMP8. CLP impaired the SC-CA1 LTP in SAMR1 compared to the sham-operated controls, but not in SAMP8. Moreover, CLP decreased the input-output curve and increased the paired-pulse ratio in SAMP8, suggesting the reduced probability of basal synaptic transmission due to sepsis. Immunohistochemical analysis revealed that CLP elevated IL-1β levels, especially in the hippocampi of SAMP8 with microglial activation. In vivo peripheral IL-1 receptor antagonist (IL-1ra) administration in the septic SAMP8 revealed that the neuroinflammation was not correlated with the peripheral elevation of IL-1β. Ex vivo IL-1ra administration to the hippocampus ameliorated LTP impairment in SAMR1 and the reduction in basal transmission in SAMP8 after sepsis. Conclusions: The mechanism of the modulation of synaptic transmission and synaptic plasticity by the acute stage of sepsis differed between SAMR1 and SAMP8. These changes were related to centrally-derived IL-1 receptor-mediated signaling and were accompanied by microglial activation, especially in SAMP8.